LESSON LEARNED FROM THE UNITED STATES: IMPROVING HEALTH COVERAGE IN A PRIMARY CARE - Komang Triyani Kartinawati; Luh Gede Pradnyawati; Doug Campos-Outcalt; Gail P Barker (Universitas Airlangga, 2022)
The universal health coverage in Indonesia is organized by Badan Penyelenggara Jaminan Kesehatan (BPJS) which gives a health protection to population as in medical insurances. This health coverage is essential to protect and maintain the quality of health in Indonesian population. However, there were some burden for universal health coverage, including the accessible to National Health Insurance (JKN). Therefore, we may learn on improving health coverage from the United States which is well known for the Medicare and Medicaid, —the center of the US medical insurances. There are at least three main lessons to learn from the medical insurance in the US, such as enrollment for medical insurance, sliding fee discount program, and cost analysis for fee-for-service in a health care. Despite the difference of health system and population between the United States and Indonesia, these lessons could be tailored for reducing burden to the universal health coverage in Indonesia.